Role of India Post in Channelizing Rural Postal Life Insurance in Rural Areas- A Study in Ramanagara District - Nandisha, H. D.; Harshitha, D. K. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
In India is second place in world population, and also 68.84% of the rural population of the India. Rural area formed a low population density and small settlement, agricultural area commonly and area such as forest. So Indian post office start a scheme to rural area to improvement and development of the rural area also rural area’s people. The “scheme is rural postal life insurance” (RPLI) in India, the Malhotra committee had observed in 1993 only 22% of the insurable population in this country had been insured and 10% of household saving. The government accepted the recommendation of Malhotra committee and allowed postal life insurance. The postal life insurance scheme (RPLI) introduced in1995 for rural peoples of India. The Government of India main objective of introduced scheme is to help a rural area and rural area people and also weaker section and rural women workers.